Hello, Mrs. Piggle-Wiggle - MacDonald, Betty Bard.; Knight, Hilary. (Lippincott, 1957)
A woman with a magic way of curing children's bad habits tries her hand with a bully, a whisperer, and a slowpoke and formulates cures for a show-off and a crybaby.
A woman with a magic way of curing children's bad habits tries her hand with a bully, a whisperer, and a slowpoke and formulates cures for a show-off and a crybaby.